Risk Factors for Postoperative Encephalopathies in Cardiac Surgery - A. N. Shepelyuk; T. V. Klypa; Yu. V. Nikiforov (Общая реаниматология)
Objective: to reveal risk factors for postoperative neurological complications (PONC) during surgery under extracorporeal circulation (EC). Subjects and methods. Five hundred and forty-eight patients were operated on under EC. Multimodality monitoring was performed in all the patients. Pre-, intra-, and postoperative data were analyzed. Results. Two patient groups were identified. These were 1) 59 patients with PONC and 2) 489 patients without PONC. The patients with PONC were older than those without PONC (61.95±1.15 and 59±0.4 years) and had a smaller body surface area (1.87±0.02 and 1.97±0.01 m2); in the PONC group, there were more women (37.3±6.4 and 22.1±1.9%). In Group 1, comorbidity was a significantly more common indication for surgery (33.9±6.22 and 9.2±1.29%). In this group, cerebral oxygenation (CO) was significantly lower (64±1.41 and 69.9±0.38%). In the preoperative period, there were group differences in hemoglobin (Hb), total protein, creatinine, and urea (135±2.03; 142±0.71 g/l, 73±0.93; 74.9±0.3 mmol/l, 104.7±3.3; 96.3±1.06 mmol/l, 7.5±0.4; 6.5±0.1 mmol/l, respectively). The PONC group more frequently exhibited more than 50% internal carotid artery (ICA) stenosis (28.8±5.95; 15.3± 1.63%; р<0.05), dyscirculatory encephalopathies (DEP) (38.9±6.4 and 19.4±1.8%; р<0.05), CO, Hb, hematocrit, and oxygen delivery were lower in Group 1 at all stages. In the preperfusion period, cardiac index was lower in Group 1 (2.3±0.1 and 2.5±0.03 l/min/m2; р<0.01). In the postper-fusion period, blood pressure was lower in Group 1 (72.3±1.4 and 76.4±0.47 mm Hg; р=0.007) and higher rate was higher (92.65±1.5 and 88.16±0.49 min-1; р=0.007). Lower PCO2a was noted in Group 1. In this group, the patients were given epinephrine more frequently (33.9±6.2 and 20.5±1.8%; р<0.05) and in larger dosages (0.02±0.001 and 0.01±0.003 ^g/kg/min; р<0.05). Conclusion. The preoperative risk factors of CONC is female gender, lower body surface area, comorbidity, lower Hb and total protein, higher creatinine and urea, concomitant DEP, and a more than 50% ICA steno-_sis. The risk factor of PONC was lower CO values in both preoperative and intraoperative periods. A reduction in perfusion pressure, determinants of oxygen delivery determinants and hypocapnia should be avoided in risk-group patients. Key words: extracorporeal circulation, cerebral oximetry, neurological dysfunction, cerebral oxygenation.